Aggradational lobe fringes: The influence of subtle intrabasinal seabed topography on sediment gravity flow processes and lobe stacking patterns. Issue 2 (4th November 2016) - Spychala, Yvonne T.; Hodgson, David M.; Stevenson, Christopher J.; Flint, Stephen S.
Abstract: Seabed topography is ubiquitous across basin‐floor environments, and influences sediment gravity flows and sediment dispersal patterns. The impact of steep (several degrees) confining slopes on sedimentary facies and depositional architecture has been widely documented. However, the influence of gentle (fraction of a degree) confining slopes is less well‐documented, largely due to outcrop limitations. Here, exceptional outcrop and research borehole data from Unit A of the Permian Laingsburg Formation, South Africa, provide the means to examine the influence of subtle lateral confinement on flow behaviour and lobe stacking patterns. The dataset describes the detailed architecture of subunits A.1 to A.6, a succession of stacked lobe complexes, over a palinspastically restored 22 km across‐strike transect. Facies distributions, stacking patterns, thickness and palaeoflow trends indicate the presence of a south‐east facing low angle (fraction of a degree) lateral intrabasinal slope. Interaction between stratified turbidity currents with a thin basal sand‐prone part and a thick mud‐prone part and the confining slope results in facies transition from thick‐bedded sandstones to thin‐bedded heterolithic lobe fringe‐type deposits. Slope angle dictates the distance over which the facies transition occurs (hundreds of metres to kilometres). These deposits are stacked vertically over tens of metres in successive lobe complexes to form an aggradational succession of lobe fringes. Extensive slides and debrites are present at the base of lobe complexes, and are associated with steeper restored slope gradients. The persistent facies transition across multiple lobe complexes, and the mass flow deposits, suggests that the intrabasinal slope was dynamic and was never healed by deposition during Unit A times. This study demonstrates the significant influence that even subtle basin‐floor topography has on flow behaviour and depositional architecture of submarine lobe complexes. In addition, we present a new aggradational lobe fringe facies associations and recognition criteria for subtle confinement in less well‐exposed and subsurface basin fills.